2018
DOI: 10.1364/boe.9.004329
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive lens-free fluorescence imaging device enabled by a complementary combination of interference and absorption filters

Abstract: We report a lens-free fluorescence imaging device using a composite filter composed of an interference filter and an absorption filter, each applied to one side of a fiber optic plate (FOP). The transmission of angled excitation light through the interference filter is absorbed by the absorption filter. The auto-fluorescence of the absorption filter is reduced by the reflection from the interference filter of normally incident excitation light. As a result, high-performance rejection of excitation light is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…For more information about methods to maintain the health parameters in short term and long term imaging, the reader is referred to another reference . An example use of the equipment related to the cells‐health in optical imaging is the work reported by Sasagawa et al where they kept their imaging device in a CO 2 incubator during cell culturing for a time‐laps imaging . Another example is the work reported by Yissachar et al where they utilized a heating block for another time‐laps imaging of their organ culture system …”
Section: Cell‐on‐chip Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…For more information about methods to maintain the health parameters in short term and long term imaging, the reader is referred to another reference . An example use of the equipment related to the cells‐health in optical imaging is the work reported by Sasagawa et al where they kept their imaging device in a CO 2 incubator during cell culturing for a time‐laps imaging . Another example is the work reported by Yissachar et al where they utilized a heating block for another time‐laps imaging of their organ culture system …”
Section: Cell‐on‐chip Platformsmentioning
confidence: 99%
“…[26] An example use of the equipment related to the cells-health in optical imaging is the work reported by Sasagawa et al where they kept their imaging device in a CO 2 incubator during cell culturing for a time-laps imaging. [27] Another example is the work reported by Yissachar et al where they utilized a heating block for another time-laps imaging of their organ culture system. [28] In 2D cell cultures, the minimum light diffraction and diffusion allows a perfect collection of the microscopic images.…”
Section: Cell-on-chip Platformsmentioning
confidence: 99%
“…A lens-free imaging system is expected to be used in new applications in bio-imaging. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) This is because a conventional fluorescence microscope is large, bulky, costly, and has a limited field of view. (4,7) A lens-free imaging system, on the other hand, does not include any lenses in its design.…”
Section: Introductionmentioning
confidence: 99%
“…(4,7,9) Previous research has already shown that the fabrication of small yet high-resolution image sensors is possible for various purposes, such as observing the brain activity of rodents, (15) illuminating and detecting light in deep biological tissues for optical therapy and diagnosis, (16) and optogenetics. (17) Moreover, it is possible to insert a small image sensor in an incubator to observe cultured cells for a long period of time, (3,6,8,11,12) and also possible to develop a similar image sensor for long-term Förster resonance energy transfer (FRET) observation in a small animal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation